PROMOTING STUDENTS’ CONCEPTUAL CHANGE ON THE CONCEPT OF ECOSYSTEM THROUGH PDEODE (PREDICT-DISCUSS-OBSERVE-EXPLAIN-DISCUSS-EXPLAIN) TEACHING STRATEGY (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
This study investigated conceptual change in students’ understanding of ecosystem concept. The PDEODE (Predict-Discuss-Explain-Observe-Discuss-Explain) teaching strategy, a variant of classical POE (Predict-Discuss-Explain) was implemented during the study. Sample was 28 senior high school students in one of senior high school in Bandung. Students’ ideas about ecosystem concept were revealed by a ten questions-test called ECT (Ecosystem Conceptual Test). Conceptual change in student’s understanding of ecosystem concept was evaluated by administering ECT in pretest, posttest, and delayed posttest.Tests’ score were then analyzed quantitatively and qualitatively. One-way ANOVA test result showed statistically significant score difference (p
Keywords: Perubahan Konseptual; Konsep Ekosistem; Strategi Pengajaran PDEODE; Conceptual Change; Ecosystem Concept; PDEODE Teaching Strategy